2001
DOI: 10.1097/00000539-200112000-00046
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Effects of Stereoisomers of Ropivacaine and Bupivacaine on Cerebral Pial Arterioles in Dogs

Abstract: The differential effects of the stereoisomers of ropivacaine and bupivacaine on cerebral pial vessels could, at least in part, depend on their chirality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 16 publications
1
23
0
4
Order By: Relevance
“…These results corroborate the findings of Chang et al 20 , who demonstrated that LEVO did not exhibit a contractile effect on the rat tracheal smooth muscles. In contrast, Iida et al 21 and Mukozawa et al 9,12 have shown that LEVO was able to induce vasoconstriction in studies on dog cerebral arterioles and rat thoracic aorta, respectively. These controversial results may be attributed to the differences in the structure of the chemical agents, the vascular bed, the experimental conditions, or the species used.…”
Section: Discussionmentioning
confidence: 91%
“…These results corroborate the findings of Chang et al 20 , who demonstrated that LEVO did not exhibit a contractile effect on the rat tracheal smooth muscles. In contrast, Iida et al 21 and Mukozawa et al 9,12 have shown that LEVO was able to induce vasoconstriction in studies on dog cerebral arterioles and rat thoracic aorta, respectively. These controversial results may be attributed to the differences in the structure of the chemical agents, the vascular bed, the experimental conditions, or the species used.…”
Section: Discussionmentioning
confidence: 91%
“…Direct activity of pre-and post-capillary smooth muscle 10 , indirect release or blockade of release of vasoactive substances, blockade or activation of adrenergic receptors, and reduction in metabolic demand have been suggested 11,52,53,54 . However, none of those mechanisms seemed to be consistent.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of those mechanisms seemed to be consistent. Changes in cytoplasmic calcium, activation of lipoxigenase pathways, and differences in stereoisomerism between ropivacaine and racemic bupivacaine may play a role in the vasoactive effect of those anesthetics 11,54,55,56 . The intracellular increase in calcium ions is the initial stimulus for the contraction of smooth muscle fiber and it can occur by stretching, nervous or hormonal stimulation, and chemical changes in the environment of the fiber 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Pesquisadores descreveram que a ROPI reduz o fluxo sanguíneo capilar cutâneo de porcos, quando administrada por via subcutânea 10 . Outros estudos experimentais mostraram que este anestésico promove contração das arteríolas cerebrais de cães e reduz significativamente o fluxo sanguíneo em nervos periféricos de ratos 11,12 . Contudo, os estudos envolvendo suas propriedades farmacocinéticas são bastante divergentes, sobretudo aqueles que enveredam pela sua vasoconstrição intrínseca, sua propriedade mais relevante 11,13 .…”
unclassified
“…Outros estudos experimentais mostraram que este anestésico promove contração das arteríolas cerebrais de cães e reduz significativamente o fluxo sanguíneo em nervos periféricos de ratos 11,12 . Contudo, os estudos envolvendo suas propriedades farmacocinéticas são bastante divergentes, sobretudo aqueles que enveredam pela sua vasoconstrição intrínseca, sua propriedade mais relevante 11,13 . Assim, este estudo teve como objetivo avaliar os efeitos da ROPI sobre a reatividade vascular em artéria mesentérica isolada de rato, além de comparar este efeito com o efeito induzido pela LIDO e avaliar o possível envolvimento do endotélio vascular e dos canais para K + nessa resposta.…”
unclassified